A risk assessment methodology for combining marine renewables with other blue economy activities via multi-use of spaces and platforms - Ruth Callaway (Proceedings of the 12th European Wave and Tidal Energy Conference 27th Aug -1st Sept 2017, Cork, Ireland, 2017)
The future growth of maritime activities may be limited due to competition for space as coastal areas become overcrowded. This has led to interest in promoting more efficient and sustainable use of the sea and its resources through the sharing of space. The MARIBE (MARine Investment for the Blue Economy) project investigated the potential of combining marine renewable energy technologies with other emerging industries. The project assessed potential combinations, and identified challenges including the perception of risk due to the combination of new technologies. This work documents the methodology used to assign the risks to various potential combination projects within the blue economy, and applies it to one of the MARIBE case studies: combining wave energy with aquaculture. A standardised methodology of risk assessment was developed comprising three core elements of the risk management process: risk identification, risk analysis and risk mitigation. This method could be applied to each potential project combination, allowing results to be directly comparable, and allowing all stakeholders to have a full understanding of the risks identified. By using a standardised methodology, critical risks could be identified and mitigated, allowing informed decisions to be made on the most suitable combination projects to pursue. The methodology can be applied to other combination projects within these sectors.